(untitled) (Fiep Bulletin - online, 2014)
The aim of the study was to design assessment methods of game performance and game skills for school basketball. The assessment method of game performance was constructed on the basis of reliable and valid measurement instruments in team sports, Game Performance Assessment Instrument and Team Sport Assessment Procedure, which enable teachers to evaluate the ability to solve tactical problems by making decisions, moving appropriately and executing skills. Three experts were engaged to verify the reliability of the method by observing and coding performance behaviours in basketball matches through digital recording. Kendall‘s coefficient was used to evaluate the data. Game abilities were measured by Under basket shot test, Dribbling and Push pass for accuracy test. Reliability was verified by test – retest method on a sample of 263 pupils in the age of 14 to 18 years. Methods of statistical analysis, intraclass correlationand standard test’s error were used to evaluate the data. Reliability of the assessment method of game performance was W=0.86 (p<0.05). The reliability of basketball tests was: Push pass for accuracy r=0.74, Under basket shot r=0.84, and Dribbling r=0.95 (all p<0.01). The reliability of all measurement instruments have been considered as a sufficient and thus recommended for practical application in teachinglearning process and for research purposes. Acknowledgment: The study is a part of the grant VE GA 10386/13 “Learning effects of different teaching approaches to sports ames in relation to gender, age and game experience” and the grant of Comenius University UK /392/2013 “Standardization of assessment method of game performance and selected motor tests of game skills in basketball and Frisbee ultimate”.